Analisis Kinerja Organisasi pada Direktorat Pemberdayaan Komunitas Adat Terpencil dan Kewirausahaan - Pratama, M Luksor (Universitas Prof. Dr. Moestopo (Beragama), 2025)
Government organizations are required to deliver high-quality and accountable public services, particularly units that directly engage with beneficiary communities, such as the Directorate of Remote Indigenous Community Empowerment and Social Entrepreneurship of the Ministry of Social Affairs of the Republic of Indonesia. Improving organizational performance is a crucial element of public sector accountability. This study aims to analyze organizational performance through the implementation of the Government Performance Accountability System (SAKIP) in order to assess the quality of performance accountability and identify areas requiring improvement. A qualitative approach was employed, with data collected through interviews, observations, and documentation studies involving key informants and performance-related supporting data. Data analysis was conducted using data reduction, data display, and conclusion drawing techniques. The findings indicate that organizational performance improvement is influenced by several key factors, including organizational restructuring due to bureaucratic simplification policies, limited human resource development and succession planning in performance data management, and the implementation of performance-based budgeting, which is categorized as moderately effective. Furthermore, the analysis of SAKIP implementation reveals a decline in overall quality compared to the previous year, particularly in performance planning and measurement aspects, while performance reporting shows notable improvement.